2018
DOI: 10.1063/1.5032174
|View full text |Cite
|
Sign up to set email alerts
|

Voltage dependent STM imaging of inorganic adsorbates

Abstract: Scanning tunneling microscopy is sensitive to surface adsorbates to a much lower impurity level than most other surface science techniques. Even under the best vacuum and preparation conditions, a very low concentration of depressions of unknown origin is often observed in STM images of the coin metal surfaces. We outline a procedure to identify impurities by apparent height spectroscopy; a technique that can be easily performed by standard scanning tunneling microscopes. Apparent height spectroscopy, performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…[23][24][25] It has been proposed recently that such voltage-dependent imaging can be used as a tool to differentiate between adsorbates on surfaces. 10 To this end, one must either have a basis of past experimental work for comparison, or confidence that theoretical work can make reliable predictions. In this paper we focus on STM images of S atoms on the three low-index surfaces of Ag.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] It has been proposed recently that such voltage-dependent imaging can be used as a tool to differentiate between adsorbates on surfaces. 10 To this end, one must either have a basis of past experimental work for comparison, or confidence that theoretical work can make reliable predictions. In this paper we focus on STM images of S atoms on the three low-index surfaces of Ag.…”
Section: Introductionmentioning
confidence: 99%
“…Depressions and protrusions are randomly distributed across the surface (Figure a,b). At the tunneling parameters used here, water and CO are imaged on Cu(111) as protrusions and depressions, respectively. Previous work revealed that water and CO monomers preferentially adsorb at atop adsorption sites on most metal surfaces, including Cu(111).…”
mentioning
confidence: 99%